E-cigarette marketing in UK stores: an observational audit and retailers' views. Issue 9 (11th September 2015) - Eadie, D; Stead, M; MacKintosh, A M; MacDonald, L; Purves, R; Pearce, J; Tisch, C; van der Sluijis, W; Amos, A; MacGregor, A; Haw, S
Abstract : Objectives: To explore how e-cigarettes are being promoted at point of sale in the UK and how retailers perceive market trends. Setting: Fixed retail outlets subject to a ban on the display of tobacco products. Participants: Observational audit of all stores selling tobacco products (n=96) in 4 Scottish communities, conducted over 2 waves 12 months apart (2013–2014), and qualitative interviews with small retailers (n=25) in 4 matched communities. Primary and secondary outcome measures: The audit measured e-cigarette display characteristics, advertising materials and proximity to other products, and differences by area-level disadvantage. Interviews explored retailers' perceptions of e-cigarette market opportunities and risks, and customer responses. Results: The number of e-cigarette point-of-sale display units and number of brands displayed increased between waves. E-cigarettes were displayed close to products of interest to children in 36% of stores. Stores in more affluent areas were less likely to have external e-cigarette advertising than those in deprived areas. Although e-cigarettes delivered high profit margins, retailers were confused by the diversity of brands and products, and uncertain of the sector's viability. Some customers were perceived to purchase e-cigarettes as cessation aids, and others, particularly low-income smokers, as a cheaper adjunct to conventional tobacco. Conclusions: E-cigarette point-of-sale displays and number of brands displayed increased over 12 months, a potential cause for concern given their lack of regulation. Further scrutiny is needed of the content and effects of such advertising, and the potentially normalising effects of placing e-cigarettes next to products of interest to children.